Analysis of the ability to interpreting information in algebraic critical thinking - Agoestanto, Arief; Sukestiyarno, YL; Isnarto, Isnarto; Rochmad, Rochmad (Unnes Journal of Mathematics Education, 2019)
This research aimed to describe the ability to interpret the information in the student's algebraic critical thinking. The type of research is a mixture of quantitative and qualitative. Methods of data collection are tests and interviews. The results of the algebraic critical thinking test referring to Watson-Glaser were analyzed descriptively quantitatively, then 6 subjects were selected each of 2 subjects including the upper, middle, and lower groups for interviews. Triangulation was carried out using 2 different subjects for each level and comparison of test results and interview results. The results of this research indicate the average Algebraic Critical Thinking ability of 31 students was 50.14 and the standard deviation was 9.09, with the lowest average inference ability was 32.64, and the highest average argument was 62.63; the correlation coefficient of algebraic critical thinking skills with indicators of inference, recognition assumptions, deductions, interpretations, evaluations of arguments, each of which amounted to 0.3264, 0.5126, 0.5417, 0.4602, 0.6263; and that the upper group subjects were able to interpret information in the medium category, the middle group subjects were able to interpret information in the medium category, and the lower group subjects were able to interpret the information in the low category.